A Comprehensive Value Chain Analysis of Mango Production and Distribution in Saptari District, Nepal - Teyung, Puja; Luitel, Gaurab (International Journal of Applied Sciences and Biotechnology, 2023)
Mango is an important fruit crop grown widely in the Saptari district of Nepal. A study was conducted in March and June 2022 under PMAMP-PIU (Prime Minister Agriculture Modernization Project-Project Implementation Unit), Saptari (PMAMP-PIU, 2074/75) to analyze the value chain of Mango in Saptari, which explored the functional and economic linkage among the actors. A total of 60 producers, 10 traders, 5 retailers and 2 key informants were interviewed. Data regarding production, post-harvest handling and marketing were analyzed by using descriptive and analytical methods with SPSS (version 26) and MS Excel 2021. Qualitative and quantitative analysis was undertaken in this study to generate insights into the limitations and opportunities of the mango value chain which can be used to establish the critical control points. The study identified key actors of Mango VC as input suppliers, producers, contract farmers, village-level collectors, wholesalers, retailers and consumers. Likewise, 4 marketing channels were identified in the study area. Economic analysis shows the cost of production per hectare was 1,453.71. Benefit cost analysis showed mango sub-sector is profitable business with BC ratio of 2.02. The average return was 2942.88/ha. The producers’ share was 55.28% in the proximal market and 32.25% in the distant market. Infestation of disease, insect and pest and lack of processing and post-harvest technology was major production problem. Int. J. Appl. Sci. Biotechnol. Vol 11(4): 197-208.